System change for economic transformation: Toward fair fiscal contracts - Katja Hujo; Ricardo Fuentes-Nieva (United Nations Research Institute for Social Development (UNRISD), 2024)
Multiple interconnected crises and unravelling social contracts have created a challenging scenario for social development, democratic governance and the achievement of the Sustainable Development Goals (SDGs). At this critical juncture, the Club de Madrid has called upon its partners to rethink social development within the context of a new eco-social contract as a pathway toward sustainable futures. As part of its 2023 Annual Policy Dialogue (APD) on "Rethinking Social Development for People and Planet," Club de Madrid has convened key partners and stakeholders to discuss potential solutions and evidence-based policy recommendations that can inform future multilateral initiatives. In preparation for the policy dialogue, three working groups have been constituted to create a platform for informed deliberations and to identify concrete and actionable recommendations for policy and governance reforms. This paper is the key output of the UNRISD-led Working Group 1 on "System Change for Economic Transformation." It focuses on fair fiscal contracts, defined as fiscal and financial arrangements that raise sufficient resources for climate action and SDG implementation and fairly distribute the financing burden within and between countries. The paper outlines pathways toward fair fiscal contracts, looking at domestic resource mobilization (DRM) and public expenditure as the two sides of the fiscal contract. It then addresses issues related to ongoing or proposed reforms of the international financial architecture and creation of global fiscal and financial pacts. The final section clusters policy recommendations into four themes: (1) Fostering an enabling environment for system change; (2) Making DRM equitable, effective and sustainable; (3) Creating fair global fiscal pacts; and (4) Delivering on eco-social contracts through public investment and transformative policies.
Keywords: 330